Problemy środowiska rodzinnego dzieci z niepełnosprawnością w dobie nauczania zdalnego - Łukaszczyk-Cibiorz, Jasmina (Zeszyty Naukowe Pedagogiki Specjalnej, 2022)
The article presents problems affecting the family environment of children with disabilities in the era of distance learning. It shows the importance of the family environment in the functioning of a child with disability and the effects of distance learning. The author presents his point of view on the long-term effects of online learning.